Spiritual Deep Breathing Exercise Is Effective In Reducing Anxiety And Stabilizing Oxygen Saturation In COVID-19 Patients - Anies Muthoharoh; Rahayu Anggraini; Wesiana Heris Santy (Poltekkes Kemenkes Surakarta, 2022)
Background: Problems that arise in COVID-19 patients include, often experiencing deep anxiety characterized by fear of pain, fear of death, fear of losing personal independence, fear of losing role functions that can cause physiological changes, namely a decrease in Oxygen Saturation (SaO2). Methods: The design of this study was a quasi-experimental approach with a Pretest-Posttest Control Group Design approach. The population of all COVID-19 patients at the Surabaya A. Yani Islamic Hospital is 187 people. The sample size is 34 respondents according to the established criteria with purposive sampling technique. The intervention group was given Spiritual Deep Breathing Exercise for 15-20 minutes and the control group was given an intervention according to hospital standards for 1 week. Analysis on anxiety used the Wilcoxon Signed Rank Test and mann whitney test. The Oxygen Saturation (SaO2) used paired sample T test and independent sample T test. Results: The results of the Anxiety analysis in the intervention group obtained a p value of 0.000 and a p value of 0.197 in the control group. The results of the Oxygen Saturation (SaO2) analysis in the intervention group obtained a p value of 0.000 and in the control group a p value of 0.884. The results of the analysis on anxiety p value 0.000 and Oxygen Saturation (SaO2) value p value 0.003 between the intervention group and the control group which means there is a difference in anxiety and Oxygen Saturation (SaO2) between the intervention group and the control group. control group in COVID-19 patients. Conclusion: Spiritual Deep Breathing Exercise theory is effective in reducing anxiety and stabilizing the value of Oxygen Saturation (SaO2) in COVID-19 patients, and this technique is easy to do, so it can be applied as a nursing intervention in isolation rooms for the development of nursing science in hospitals.